C-REACTIVE PROTIEN AS A PROGNOSTIC INDICATOR FOR ISCHEMIC STROKE OUTCOMES.: http://doi.org/10.46536/jpumhs/2023/13.03.447 - Shabnam Rani1 , Nadeem Memon2 , Gordhan Das3 , Rajkumar4 , Abdul Ghani Rahimo5 , Sumaiya Amanat Ali6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
OBJECTIVES: To evaluate the value of CRP levels and their possible role in the pathogenesis of acute ischemic stroke.PATIENTS AND METHODS: This descriptive study was conducted at the medical wards of Liaquat University Hospital, Jamshoro, Hyderabad. Patients of either sex with their first-ever ischemic stroke were included. Blood samples were taken from all patients to measure the serum C-reactive protein. Blood samples were taken within 24 hours after an ischemic stroke, within 48 to 72 hours, and at hospital discharge. Relationship of C-reactive protein at different stages after acute ischemic stroke and also its role in the pathogenesis of acute ischemic stroke.RESULTS: A total of 100 patients with ischemic stroke were evaluated for CRP levels. There were 72 men and 28 women. 65% of patients had raised CRP levels at the time of admission within 12 to 24 hours after stroke, while 35% had a normal 0.5 mg/dl CRP level at the time of admission. Out of 65% of patients, the level of CRP persistently rose until discharge in 46% of patients, while the level dropped to normal in the remaining 19% of patients. Higher CRP levels at the time of admission were associated with large infarct sizes. Deaths were also observed in patients with a CRP level greater than 1.5mg/dl within 12 to 24 hours of stroke.Conclusion: CRP observed to be the helpful tool for assessing the prognosis of ischemic stroke patients. This is attributed to its capability to signify the systemic inflammatory response within the body, and its consistent link with unfavorable outcomes.